Kindred - Butler, Octavia E. (Black women writers series., 2004)
"Dana, a modern black woman, is celebrating her twenty-sixth birthday with her new husband when she is snatched abruptly from her home in California and transported to the antebellum South. Rufus, the white son of a plantation owner, is drowning, and Dana has been summoned across the years to save him. After this first summons, Dana is drawn back, again and again, to the plantation to protect Rufus and ensure that he will grow to manhood and father the daughter who will become Dana's ancestor. Yet each time Dana's sojourns become longer and more dangerous, until it is uncertain whether or not her life will end, long before it has even begun" --AbeBooks.